Histological Description of Skeletal Muscles of Wistar Rats Given Nephelium Lappaceum Extract - Lukman Fajar Setyawan; Elvin Clara Angmalisang; Sonny John Ruddy Kalangi (Indonesian Journal of Global Health Research, 2026)
Hyperglycemia is a condition characterized by elevated blood sugar levels, which can trigger oxidative stress and cause cellular damage, including to skeletal muscle cells. The antioxidant content in rambutan leaf extract can lower blood sugar levels. This study aims to determine the histological features of skeletal muscle of Wistar rats given rambutan leaf extract after alloxan induction. Method: This study used a laboratory experimental design with a post-test only control group design. A total of 20 Wistar rats were randomly divided into four groups: a negative control group, a positive control group, and treatment groups administered rambutan leaf extract at doses of 25 mg/kg body weight and 50 mg/kg body weight. Data were collected through blood glucose level measurements, examination of histopathological specimens of skeletal muscle stained with hematoxylin and eosin (H&E), and measurements of muscle fiber diameter. The data were analyzed descriptively by comparing histological findings, blood glucose levels, and mean muscle fiber diameters across groups. Group A experienced a decrease in the average diameter of muscle fibers to 49.06 mm (longitudinal) and 70.45 mm (transverse) accompanied by morphological changes in the form of wavy skeletal muscle fibers. Group B showed improvements in muscle fiber structure with an average diameter approaching normal, namely 59.35 mm (longitudinal) and 91.35 mm (transverse). Group C saw an increase in the average diameter of muscle fibers to 100.97 mm (longitudinal) and 130.21 mm (transverse) indicating a tissue protective effect. Group D showed an average diameter of muscle fibers of 29.47 mm (longitudinal) and 54.34 mm (transverse) accompanied by wavy skeletal muscle fibers. Administration of rambutan leaf extract at a dose of 25 mg/kgBW to Wistar rats increased the average diameter of skeletal muscle fibers and maintained the basic structure of skeletal muscle tissue. Administration of rambutan leaf extract at a dose of 50 mg/kgBW showed wavy skeletal muscle fibers and a decrease in the average diameter of skeletal muscle fibers.